A comparison of the time scales accessible and kinetic discrimination obtainable using steady-state voltammetry at common hydrodynamic and microelectrode geometries - Alden, J; Hakoura, S; Compton, R (1999)
The kinetic discrimination of steady-state voltammetry at microdisk, microhemispherical, rotating disk, channel (microband), wall-jet, and wall- tube electrodes was compared by measuring the broadness of numerically simulated ECE and EC2E working curves and superimposition of numerically simulated EC and EC2 working curves by equating the average diffusion thicknesses. This together with the range of time scales calculated from the span of typical experimental parameters (electrode size, flow rate, etc.) allows the range of rate constants measurable with each geometry to be compared.